Dual-Task Treadmill Training for the Prevention of Falls in Parkinson's Disease: Rationale and Study Design - Mylius, Veit; Maes, Laura; Negele, Katrin; Schmid, Christine; Sylvester, Ramona; Brook, Caroline Sharon; Brugger, Florian; Perez-Lloret, Santiago; Bansi, Jens; Aminian, Kamiar; Paraschiv-Ionescu, Anisoara; Gonzenbach, Roman; et al. (Frontiers in Rehabilitation Sciences, 2022)
Various factors including fear of falling, postural instability, and altered executive function contribute to the high risk of falling in Parkinson´s disease (PD). Dual task training is an established method to reduce this risk. Motor-perceptual task combinations typically require a patient to walk while simultaneously engage in a perceptual task. Motor-executive dual tasking combine locomotion with executive function tasks. One augmented reality treadmill training (AR-TT) study revealed promising results of a perceptual dual task training with a markedly reduced frequency of falls especially in PD patients. We here propose to compare the effects of two the types of concurrent tasks, perceptual and executive, on high intensity treadmill training (TT). Patients will be trained with TT alone, in combination with an augmented reality perceptual dual tasking (AR-TT) or with an executive dual tasking (Random Number Generation; RNG-TT). The results are expected to inform research on therapeutic strategies for training of balance in PD.